ANALISIS KEGIATAN PROGRAM KREATIVITAS MAHASISWA KEWIRAUSAHAAN (PKM-K) PEMANFAATAN LIMBAH RUMAH TANGGA (KALENG, KACA, STYROFOAM, KARDUS, KULIT TELUR) - Neta Dian Lestari; Ayu Febrianti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Seeing the condition of our environment which is disputed every day by waste which is increasingly mounting as if this waste is the main problem faced by the government and society. So that people in several countries and even all over the world are competing to solve this problem. If we talk about this waste problem, actually this waste has many benefits including making home decorations, eye cendra, and souvenirs (typical gifts of ASIAN GAMES). Implementation methods carried out in carrying out PKM-K activities Utilization of Household Waste (Cans, Glass, Styrofoam, Cardboard, Eggshells), that consists of some Stages: Preparation, Production, Marketing, Achieving Objectives, Evaluations and Reports. Based on the marketing results of several bazaar activities, the conclusion was that PKM-K Utilization of Household Waste is very beneficial for the surrounding environment because it can recycle waste into creative products. Based on the results of this utilization, PKM-K activities can generate benefits for students financially, the profit obtained from waste treatment is 73.73%.